Literasi Media Sosial Humas Pemerintah Daerah - Putra, Novian Anata (Informasi, 2017)
Nowadays, the government is trying to fight against hoax. One of them, President Joko Widodo instructed to improve the function of government public relations and information managers to ward off hoaxes spread quickly in social media. However, it will work if government public relations officers have adequate social media literacy skills. Social media literacy is considered the basis for understanding the characteristics of new media. The aim of this research is to examine the level of social meda literacy among local government public relations at present. Quantitative approach with survey method will be used in this research. The study was conducted in eight local governments that have held anti-hoax declarations. The eight local governments are: Semarang regency, Semarang city, Wonosobo regency, Solo city, Banyumas regency, Blora regency, Yogyakarta city and Province of Bali. Based on the research analysis, it can be concluded that the managers of social media public relations of local governments who have held anti-hoax declaration are already have enough social media literacy. The local government needs to increase knowledge and skills that are technical about new media and social media in order to optimize the function and the role of local government public relations in the effort to ward off hoaxes. While the hardest part of social media literacy, which always involves the criticality literacy media, most of local government public relations have already master it. Pemeritah saat ini berusaha melawan berita-berita hoax. Salah satunya, Presiden Joko Widodo menginstruksikan untuk meningkatkan fungsi humas pemerintah dan pengelola informasi untuk menangkal hoax yang tersebar cepat di media sosial. Namun, hal itu akan berhasil jika para petugas humas pemerintah mempunyai kecakapan literasi media sosial yang memadai. Literasi media sosial dianggap sebagai dasar memahami karakteristik media baru. Penelitian ini akan melihat sejauh mana tingkat literasi media sosial di kalangan humas pemerintah daerah saat ini. Penelitian menggunakan pendekatan kuantitatif dengan metode survei. Penelitian dilakukan di delapan pemerintah daerah yang telah menggelar deklarasi anti hoax, yakni Kota Semarang, Kabupaten Semarang, Kabupaten Wonosobo, Kota Solo, Kabupaten Banyumas, Kabupaten Blora, Kota Yogyakarta, dan Provinsi Bali. Dengan tidak adanya nilai rendah, maka dapat disimpulkan bahwa para pengelola media sosial humas pemerintah daerah yang telah menggelar deklarasi anti hoax telah memiliki literasi media sosial yang cukup. Untuk mengoptimalkan fungsi dan peran humas pemerintah daerah dalam usaha menangkal hoax hanya perlu meningkatkan pengetahuan dan ketrampilan yang sifatnya teknis tentang media baru dan media sosial. Sedangkan bagian tersulit dari literasi media sosial, yaitu selalu melibatkan tingkat kekritisan para pegawai humas pemerintah daerah dalam aktifitas media sosial, telah banyak yang menguasainya.